Forecasting of hydropower production using Box-Jenkins model at Tasik Kenyir, Terengganu - Nornabila, Abu; Nurul Nadrah Aqilah, Tukimat; Noratikah, Abu (AIP, 2024)
Hydropower is one of the most essential mainstays in the long list of renewable energy resources that implements the use of potential energy of water to generate power by transforming the energy in the form of electricity. Forecasting the future energy production benefits in maintaining the effectiveness of the hydropower plant in the long term. This study aims to forecast the hydropower energy produced as electricity in Sultan Mahmud Hydropower Plant, Lake Kenyir, Terengganu using Box-Jenkins model in the short term from October 2020 until December 2022. Analysis and forecast is based on the historical data from a total of four unit of electricity generator from January 1997 to September 2020. Evaluation is made on the forecasted result using Mean Absolute Percentage Error (MAPE) to validate the accuracy of the model. The results demonstrated that by using the proposed model and numerical calculation, Box-Jenkins model is effective in forecasting the monthly electricity energy produced by the hydropower plant. The best model obtained with the smallest MAPE value of 26.4% is ARIMA (2,0,0).